Role of a Sacred Grove in Conservation of Plants - Bhakat, R. K.; Sen, U. K.; Pandit, P. K. (Indian Forester, 2008)
Many traditional conservation ethics of people directly or indirectly protect forest patches by dedicating them to local deities. Such forest pockets, referred to as sacred groves, are more or less small to large chunk of traditionally maintained near-virgin forests protected on sociocultural grounds. Named differently in different states of India, these groves are mainly concentrated in tribal areas and are managed by local people for various purposes. Irrespective of their origin, size and management regimes, all sacred groves are islands of biodiversity protecting a host of plant and animal species including some rare and threatened taxa. With this background, this paper attempts to highlight the role played by a 4-acre sacred grove (popularly known as'Sitabala than') of West Midnapore District in West Bengal towards conservation of plant diversity. The study records 80 species of angiosperms covering 42, 10, 16 and 12 species of herbs, shrubs, trees and climbers respectively. Moreover, the grove supports few locally useful medicinal plants. Owing to protection offered on socio-religious grounds, the sacred grove provides optimum conditions congenial for the growth of plants. As a result, some of the trees attain maximum dimensions in terms of size and growth patterns. Therefore, there is an urgent need not only to protect the sacred forest, but also to revive and reinvent such traditional way of nature conservation.